Teacher training literacy teachers: the prospect of alfabetizar. Letrando-advances and challenges - Alves, Vera Souto (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This article is the fruit of experience and reflection while Continuing training programmes training of Teachers Teachers released by the Ministry of Education-Teacher-training program for Teachers, Teachers in 2001 and Pro-Literacy-Continued training programme for teachers of Years/Initial Series of elementary school, in 2007; in the municipalities of Earl and Alhandra-PB, administered through the departments of Education and also as school supervisor who accompanied the pedagogical practice of teachers teacher students of PNAIC-National Pact For Literacy at the right age, in 2013; This course is in progress in the municipalities, the same aims to meet the goal set out in PNE. Is intended for teachers of public networks that are in teaching exercise in cycles of elementary literacy. The purpose here is to portray the proposal of this course (PNAIC), your conception of literacy and literacy, aiming at a better understanding and the repercussions on teaching practice, reporting the challenges and advances, observed in this didactic transposition.